Prevalence of anti-sperm antibodies in mares in the south-eastern Anatolian of Turkey - Risvanli, A; Cetin, H; Apaydin, AM; Korkmaz, O; Atli, MO; Timurkan, H (Natl Veterinary Research Inst, 2005)
This study aimed to determine the prevalence of anti-sperm antibodies (ASAs) in mares in the south-eastern Anatolian of Turkey and the effect of age, mating number, pregnancy status and metritis on the antibody prevalence. One hundred and fifty-seven purebred Arabians and 19 Thoroughbreds were included in the study. The presence of ASAs in blood sera of the animals was determined by enzyme immunoassay. The percentage of animals with ASAs in their serum was 10.23. The prevalence of ASAs was the lowest in mares that had been mated three or more times. There were no differences between the groups when the results were assessed according to age, pregnancy and uterine mucosa status.
Keywords: mare; anti-sperm antibodies